2011
DOI: 10.1007/s10147-010-0170-6
|View full text |Cite
|
Sign up to set email alerts
|

High-dose dexamethasone plus antihistamine prevents colorectal cancer patients treated with modified FOLFOX6 from hypersensitivity reactions induced by oxaliplatin

Abstract: Increased doses of dexamethasone and antihistamine significantly reduced oxaliplatin-related hypersensitivity reactions. This effective approach should be considered for all patients who receive FOLFOX, allowing treatment to be completed as planned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 18 publications
0
27
0
Order By: Relevance
“…Hypersensitivity reactions during oxaliplatin infusion are major problem associated with its use (Kidera et al, 2011). Hypersensitivity reactions can be the cause of discontinuation of oxaliplatin infusion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hypersensitivity reactions during oxaliplatin infusion are major problem associated with its use (Kidera et al, 2011). Hypersensitivity reactions can be the cause of discontinuation of oxaliplatin infusion.…”
Section: Discussionmentioning
confidence: 99%
“…Hypersensitivity reactions can be the cause of discontinuation of oxaliplatin infusion. There have been limited reports on the characteristics and the risk factors of oxaliplatin-related hypersensitivity reactions, and adverse reactions would be important with extensive use of oxaliplatin (Kidera et al, 2011;Kim et al, 2009;Polyzos et al, 2009;Shao et al, 2010;Shibata et al, 2009). In addition, there is not perfect tool to predict oxaliplatin-related hypersensitivity reactions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A small retrospective study showed that premedication (diphenhydramine, dexamethasone, granisetron, and famotidine vs. dexamethasone and granisetron) reduced hypersensitivity reactions associated with modified folfox6 (leucovorin, 5-fluorouracil, oxaliplatin) 46 . In the case of a grade 1 or 2 hypersensitivity reaction, it is possible to continue oxaliplatin treatment without reducing the infusion rate if the patient is premedicated with dexamethasone 47 .…”
Section: Skin Testingmentioning
confidence: 99%